(3GdhSjdI GdGMeOjI hGdPQjYI GdSQeOjI aj TQM GdWQjbI GdeMeOjIs - (3GdBeOj GdbjUQj, QLH Hf CMeO, HYO (B1087 (3g`s ((3MSf Hf ehSi Hf MSjf chedLfg hjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj gOGfG deYQJg Gdbhje deG cGf GdcJGH GdeSei HGdWQjbI GdeMeOjI hGdSjQI GdCMeOjI ddTjN eMeO GdHQchj cJGHG LGeYG dCUfGa GdaVGFd eMJhjG Ydi CfhGY GdWGYGJ ef GdaQhV hGdfhGad s
(3BNQgG (B:s
(3hGdKGdKI LdGA GdbdhH hbO YdeJ MGd HYVgG eeG bQQfG BfaG aJCed aYdjc CjgG GdSGdc HgG hWGdYgG dJNQL HeYQaI OdGFdgG Yf GdJbdjO GdQhj ceG bGd MJi fYde MbjI ebGdfG Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3/18s
(3cTa GdXfhf (B2/1112s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs